Research in Medical College: Raison d’Etre - Yunus, Emran Bin (Journal of Chittagong Medical College Teachers’ Association, 2009)
doi: 10.3329/jcmcta.v18i1.3810 Journal of Chittagong Medical College Teachers' Association 2007: 18(1):1-2